Early Life Exposure to Air Pollution and Autism Spectrum Disorder: Findings from a Multisite Case–Control Study. Issue 1 (January 2020) - McGuinn, Laura A.; Windham, Gayle C.; Kalkbrenner, Amy E.; Bradley, Chyrise; Di, Qian; Croen, Lisa A.; Fallin, M. Daniele; Hoffman, Kate; Ladd-Acosta, Christine; Schwartz, Joel; Rappold, Ana G.; Richardson, David B.; et al.
Abstract : Background: Epidemiologic studies have reported associations between prenatal and early postnatal air pollution exposure and autism spectrum disorder (ASD); however, findings differ by pollutant and developmental window. Objectives: We examined associations between early life exposure to particulate matter ⩽2.5 µm in diameter (PM2.5 ) and ozone in association with ASD across multiple US regions. Methods: Our study participants included 674 children with confirmed ASD and 855 population controls from the Study to Explore Early Development, a multi-site case–control study of children born from 2003 to 2006 in the United States. We used a satellite-based model to assign air pollutant exposure averages during several critical periods of neurodevelopment: 3 months before pregnancy; each trimester of pregnancy; the entire pregnancy; and the first year of life. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs), adjusting for study site, maternal age, maternal education, maternal race/ethnicity, maternal smoking, and month and year of birth. Results: The air pollution–ASD associations appeared to vary by exposure time period. Ozone exposure during the third trimester was associated with ASD, with an OR of 1.2 (95% CI: 1.1, 1.4) per 6.6 ppb increase in ozone. We additionally observed a positive association with PM2.5 exposure during the first year of life (OR = 1.3 [95% CI: 1.0, 1.6] per 1.6 µg/m 3 increase in PM2.5 ). Conclusions: Our study corroborates previous findings of a positive association between early life air pollution exposure and ASD, and identifies a potential critical window of exposure during the late prenatal and early postnatal periods. Abstract : Supplemental Digital Content is available in the text.